Experimental Analysis and Optimization of Tribological Properties of Self-Lubricating Aluminum Hybrid Nanocomposites Using the Taguchi Approach - Vinoth Kumar Selvaraj; S. Jeyanthi; Raja Thiyagarajan; M. Senthil Kumar; L. Yuvaraj; P. Ravindran; D. M. Niveditha; Yigezu Bantirga Gebremichael (Advances in Materials Science and Engineering)
In recent times, tribological properties are gaining and grabbing great attention in metal matrix composites. They can provide significant benefits such as a lower coefficient of friction, wear resistance, high strength, and stiffness. Considering all these parameters, this research article mainly focuses on developing an aluminum hybrid nanocomposite material fabricated by powder metallurgy. Then, the results were examined using a pin-on-disk apparatus. Further optimization techniques such as the Taguchi approach under Design of Experiments have been adopted to obtain a minimal outcome of various assumed parameters such as A. percentage weight fraction of graphite content (Gr), B. the sliding distance, C. the sliding speed, and D. the stress applied. In addition, we have chosen parameters such as friction and wear loss for optimizing the outcome, including the main effect plots for the S-N ratio and the Analysis of Variance (ANOVA) approach. Based on the experimental results, we have noticed that friction and wear loss coefficient increase with increased applied load and sliding distance. Also, it was noted that there was a slight decrease in the coefficient of friction and wear loss when an increment was made in the graphite content, respectively. It was perceived that the sample containing 10% of graphite (Gr) could create a self-lubricating effect that significantly reduced wear loss and the coefficient of friction. Finally, by considering all these achieved results, aluminum nanocomposites can be employed in automobile, defense, and aerospace applications as they can reduce the weight of the components with improved wear behavior and more thermal stability.